Rational Extremism The Political Economy of Radicalism - Wintrobe, Ronald (Cambridge University Press, 2013)
Extremist movements often appear mysterious, frightening, and irrational. Extremists like Osama bin Laden are said to be different from us: they are twisted, deviant, fanatical, or simply “evil.” One reason, of course, is the extraordinary destruction of which they are sometimes capable, as symbolized by the events of 9/11. Another reason is the apparently single-minded passion of their leaders. And while the leaders of these movements often appear dogmatic, perhaps even more frightening is the oft-observed fanatical loyalty of their followers.